(untitled) (Journal of Libya for geographical studies, 2026)
This study aims to analyze annual, seasonal, and monthly temperature records at the Tripoli meteorological station over the period 1919–2020, in order to detect indicators of change in temperature trends, whether increasing or decreasing. The analysis is based on monthly data of minimum, maximum, and dry-bulb temperatures. Several statistical methods commonly used in climatological studies were employed, including cumulative sums (CUSUM), the t-test, moving averages, and simple linear regression, to identify statistically significant trends in annual, seasonal, and monthly temperature averages in the study area at a significance level of less than 0.05. The results revealed the presence of a positive thermal trend in annual, seasonal, and monthly minimum, maximum, and dry-bulb temperatures, with statistical significance at the 0.05 level across all seasons and months in the Tripoli region.